Financial and Asset Management of Higher Education (A Comparative Study of Universities with Legal Entities-PTNBH) - Wicaksono, Arif; Idris, Idris (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2025)
This research aims to analyze the financial and asset management practices of universities transitioning to PTN-BH status. Employing a qualitative descriptive approach, data collection was conducted through in-depth interviews, documentation, and field observations, complemented by secondary data from relevant sources. The data analysis followed the Miles and Huberman model. The findings reveal that PTN-BH institutions successfully manage financial resources and investments through structured planning in their Annual Work and Budget Plans, aligning financial goals with faculty targets. Additionally, these institutions optimize asset utilization by engaging in economic activities such as facility leasing and renting out buildings, which significantly contribute to institutional income. This study underscores the importance of efficient financial and asset management practices, providing a reference model for universities undergoing the transition to PTN-BH status. The results also highlight the potential for future research to refine and expand these practices, ensuring continuous improvement in the management of PTN-BH institutions.